VPQ-E: Cultural adaptation into Spanish of the Voice Performance Questionnaire - Velandrino Nicolás, Antonio; Cabello Luque, Francisco; Parra Villazala, María; Belchi Serrano, Natalia del Rosario (Revista de Investigación en Logopedia, 2019)
The Voice Performance Questionnaire (VPQ) is a self-report instrument for patients with dysphonia which is simple, quick to apply and with good psychometric properties. The aim of this work is to carry out the cultural adaptation of the Spanish version of the VPQ in dysphonic Spanish population. The questionnaire was translated by three experts in speech-therapy, and then back-translated by two native translators who were not aware of the goal of the study. After the comparison of the translation, a previous version of the instrument was produced and applied in a sample with 45 patients with dysphonia. Due to applicability problems, a response option was modified for one of the items. Initial and provisional psychometric measures for internal consistency, typical measurement error, test-retest reliability and convergent validity were adequate. The cultural adaptation of the questionnaire (VPQ-E) was developed from these results, and is offered in the appendix.
Keywords: VPQ; Dysphonia; Voice disorders; Patient-reported outcomes measures; Translation